An investigation of PM10 concentrations at one site of Kuala Lumpur - Mohd. Yusoff, Mohd. Rashid (1987)
The measurement of total suspended particulate (TSP) matter and PM10 (mass of particulate with diameter less than or equal to 10 μm) concentrations were made between September 1986 – May 1987 at the Universiti Teknologi Malaysia monitoring station. On the average, the TSP concentration was 63.3 μg/m3 while the PM10 concentration was 47.6 μg/m3 or 75 percent of the TSP. Both PM10 and TSP were well collected (r = 0.92) with a positive intercept on the TSP axis. This clearly indicates that the PM10 constitutes a portion of the TSP concentration. The TSP and PM10 concentrations were higher in the weekdays than the weekend. This can be directly related to the daily human activities during the weekdays. The studies also high-lighted the impact of industrial activities on the PM10 level within the area.